Modified high-nickel ternary material, and preparation method and application thereof
Patent Information
- Application Number
- CN202211357396.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-01
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2042-11-01
AI Technical Summary
现有的这种制备技术,其工序较为繁琐,生产成本较高,且干法包覆容易造成包覆不均匀发生偏聚以及包覆剂自团聚的现象
[0053]本发明采用非金属酸类化合物和羟基氧化铝作为包覆源,使包覆液呈酸性,并且避免了湿法包覆对高镍三元材料结构的破坏,即,本发明采用湿法包覆,一方面能够中和高镍三元材料表面残碱,替代水洗工序,另一方面,作为包覆混合工序,避免了水洗后再进行混合包覆的工序,使水洗工序和包覆工序简化为了同一步骤;此外,本发明采用湿法包覆的方式,包覆效果好,避免了干法包覆不均匀和包覆剂自团聚的缺点,从而得到了结构稳定性高且循环性能优异的改性高镍三元材料。
Smart Images

Figure CN117985772B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery technology and relates to a modified high-nickel ternary material, its preparation method, and its application. Background Technology
[0002] Lithium-ion batteries have been widely used as a ubiquitous portable energy source due to their advantages such as long cycle life, high energy density, high power density, and low carbon footprint. However, their application in electric vehicles is limited, mainly because current power batteries suffer from low range, slow charging speed, and high cost, hindering their development in electric vehicles. Therefore, it is necessary to improve the energy density, power density, cycle life, and reduce the cost of lithium batteries. The energy density and cost of lithium-ion batteries largely depend on the cathode material. Among available cathode materials, high-nickel ternary cathode materials have advantages such as high capacity, high rate capability, and low cost, and are considered the most promising cathode material for improving the energy density of power batteries.
[0003] However, excessively high Ni content in high-nickel ternary materials can compromise the material's structural stability, leading to the generation of highly active Ni during charging. 4+ Reacting with the electrolyte generates a NiO-like rock salt phase, severely disrupting the structure of the layered material and causing the cathode structure to collapse. This, in turn, induces the dissolution of transition metal ions, phase transitions, and lattice oxygen evolution. In particular, changes in lattice parameters during charging and discharging of high-nickel cathode materials lead to the formation of microcracks. These microcracks expose new surfaces within the particles, further accelerating structural degradation and causing a simultaneous decrease in the thermal stability, structural stability, and cycle stability of the cathode material. Furthermore, with increasing nickel content, the residual alkali content on the material surface also increases. When exposed to air, it readily reacts with CO2 and H2O to produce Li2CO3 and LiOH on the material surface. The former causes severe gas expansion during high-temperature storage, especially during charging, while the latter reacts with LiPF6 in the electrolyte to generate HF. HF dissolves from the cathode material surface into the electrolyte via transition metal ions, leading to lattice distortion in the cathode material. All of these degradation mechanisms result in a decrease in capacity, performance, and cycle life.
[0004] To reduce the residual alkali content on the surface of high-nickel ternary cathode materials, existing technologies typically employ a water washing process. This involves washing the material with water under appropriate feed-to-liquid ratios, temperatures, rotation speeds, and times, followed by dehydration and drying. To avoid direct contact between the active material and the electrolyte, which could lead to the aforementioned side reactions, the washed material undergoes dry coating. This involves dry mixing and coating the dried powder, followed by sintering to obtain the final product. However, this existing preparation technology is complex, has high production costs, and dry coating is prone to uneven coating, resulting in segregation and self-agglomeration of the coating agent.
[0005] Based on the above research, there is a need to provide a method for preparing modified high-nickel ternary materials. This method can overcome the defects of existing dry coating methods, not only achieving good coating effects but also reducing the residual alkali value on the surface, thereby significantly improving the electrochemical performance of the modified high-nickel ternary materials. Summary of the Invention
[0006] The purpose of this invention is to provide a modified high-nickel ternary material, its preparation method, and its application. The preparation method employs a wet coating process, in which the high-nickel ternary material is dispersed and coated in a coating solution, followed by sintering. This eliminates the need for dry mixing and coating after water washing, simplifying the process of removing residual alkali and coating into a single step, thus shortening the material preparation process. Furthermore, the removal of residual alkali and the coating effect are excellent, significantly improving the electrochemical performance of the modified high-nickel ternary material.
[0007] To achieve this objective, the present invention adopts the following technical solution:
[0008] In a first aspect, the present invention provides a method for preparing a modified high-nickel ternary material, the method comprising the following steps:
[0009] (1) Mix non-metallic acid compound, aluminum hydroxide and solvent to obtain coating solution;
[0010] (2) Mix the high-nickel ternary material with the coating liquid described in step (1) to obtain a mixture;
[0011] (3) The mixture described in step (2) is calcined to obtain the modified high-nickel ternary material.
[0012] This invention first prepares a coating solution using non-metallic acid compounds and aluminum hydroxide, which is then mixed with a high-nickel ternary material. The addition of the non-metallic acid compounds not only provides an acidic environment for the coating solution, neutralizing residual alkali on the surface of the high-nickel ternary material, but also serves as a coating source, forming compounds containing non-metallic elements and aluminum with aluminum hydroxide, thereby improving the structural stability and electrochemical performance of the high-nickel ternary material. Simultaneously, the use of aluminum hydroxide as a coating source allows it to cooperate with the non-metallic acid compounds to complete the wet coating process. This simplifies the washing and coating steps of the high-nickel ternary material into a single step, thus simplifying the preparation process, improving the coating effect, effectively reducing residual alkali on the surface of the high-nickel ternary material, and significantly enhancing the electrochemical performance of the modified high-nickel ternary material.
[0013] Preferably, the non-metallic acid compound in step (1) includes boric acid.
[0014] The non-metallic acid compound described in this invention is boric acid. Since boric acid is both acidic and can neutralize residual alkali, and can also serve as a coating source to form boron-aluminum compounds with aluminum hydroxide, it can further improve the structural stability and electrochemical performance of high-nickel ternary materials.
[0015] Preferably, the aluminum hydroxyaluminate in step (1) is A-4 type aluminum hydroxyaluminate sol.
[0016] Aluminum hydroxide includes A-4 type and A-10 type. Since A-4 type aluminum hydroxide is acidic and A-10 type aluminum hydroxide is alkaline, A-4 type aluminum hydroxide, which is acidic, is selected as the coating source in order to further reduce the residual alkali value on the surface of high-nickel ternary materials and improve electrochemical performance. On the other hand, using a sol form can make aluminum hydroxide uniformly dispersed in the solvent, which can improve the coating effect.
[0017] Preferably, the content of the non-metallic acid compound in step (1) is 0.5-1.5 wt% of the mass of the high-nickel ternary material in step (2), for example, it can be 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, 1.0 wt%, 1.0 wt%, 1.2 wt%, 1.3 wt%, 1.4 wt%, or 1.5 wt%, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0018] The content of non-metallic acid compounds described in this invention is within a reasonable range, which can ensure the effects of removing residual alkali and coating. If the content of non-metallic acid compounds is too low, effective coating cannot be achieved, and the content of boron-aluminum compounds will decrease. If the content of non-metallic acid compounds is too high, the coating effect will also decrease, the proportion of ternary materials will decrease, and the electrochemical performance will also decrease.
[0019] Preferably, the content of aluminum hydroxide in step (1) is 1-3 wt% of the mass of the high-nickel ternary material in step (2), for example, it can be 1 wt%, 1.25 wt%, 1.5 wt%, 1.75 wt%, 2 wt%, 2.25 wt%, 2.5 wt%, 2.75 wt%, or 3 wt%, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0020] The content of aluminum hydroxide described in this invention also needs to be within a reasonable range. If the content of aluminum hydroxide is too low, the coating layer will be uneven, and the ternary material will undergo side reactions with the electrolyte, resulting in a decrease in electrochemical performance. If the content of aluminum hydroxide is too high, the coating layer will be too thick, which will also reduce the electrochemical performance.
[0021] Preferably, the mass ratio of the solvent in step (1) to the high-nickel ternary material in step (2) is (1-1.5):1, for example, it can be 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1 or 1.5:1, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0022] The solvent and high-nickel ternary material described in this invention will affect the coating effect. If the solvent content is too low, the coating will not be uniform, resulting in a decrease in the coating effect. The ternary material and the electrolyte will undergo side reactions, leading to a decrease in electrochemical performance. If the solvent content is too high, it will affect the structural stability of the high-nickel ternary material, thereby causing a decrease in electrochemical performance.
[0023] Preferably, step (1) of mixing the non-metallic acid compound, aluminum hydroxyacid and solvent includes: first dissolving the non-metallic acid compound with the solvent, and then adding aluminum hydroxyacid for dispersion.
[0024] Preferably, the solvent in step (1) includes water.
[0025] This invention uses water as the solvent for wet coating. Since water can dissolve non-metallic acid compounds, making the coating solution acidic, it can further improve the residual alkali removal effect. In subsequent processing, non-metallic acid compounds can be further precipitated, thereby improving the coating effect. Moreover, using water as a solvent ensures higher safety.
[0026] Preferably, the mixing time in step (1) is 8-12 minutes, for example, it can be 8 minutes, 9 minutes, 10 minutes, 11 minutes or 12 minutes, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0027] Preferably, the mixture described in step (2) is evaporated to dryness before being calcined as described in step (3).
[0028] Preferably, the evaporation temperature is 120-180℃, for example, it can be 120℃, 130℃, 140℃, 150℃, 160℃, 170℃ or 180℃, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0029] Preferably, the mixing time in step (2) is 8-12 minutes, for example, it can be 8 minutes, 9 minutes, 10 minutes, 11 minutes or 12 minutes, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0030] Preferably, the method for preparing the high-nickel ternary material in step (2) includes: mixing the high-nickel ternary material precursor, the lithium source and the doping additive, and sintering to obtain the high-nickel ternary material.
[0031] Preferably, the doping additive includes any one or a combination of at least two of ZrO2, TiO2, Nb2O5, CeO2, SrO, MgO or WO3. Typical but non-limiting combinations include combinations of ZrO2 and TiO2, combinations of Nb2O5 and CeO2, or combinations of SrO and MgO.
[0032] Preferably, the content of the doped additive is 0.05-0.5 wt% of the mass of the high-nickel ternary precursor, for example, it can be 0.05 wt%, 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt% or 0.5 wt%, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0033] Preferably, the sintering temperature is 700-800℃, for example, 700℃, 720℃, 740℃, 760℃, 780℃ or 800℃, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0034] Preferably, the sintering time is 12-16 hours, for example, 12 hours, 13 hours, 14 hours, 15 hours or 16 hours, and the heating rate is 1-3℃ / min, for example, 1℃ / min, 1.5℃ / min, 2℃ / min, 2.5℃ / min or 3℃ / min, but not limited to the listed values. Other unlisted values within the range are also applicable.
[0035] Preferably, the sintering is carried out in a pure oxygen atmosphere.
[0036] Preferably, the molar ratio of lithium in the lithium source to the total amount of nickel, cobalt and manganese metal in the high-nickel ternary material precursor is (1.01-1.05):1, for example, it can be 1.01:1, 1.02:1, 1.03:1, 1.04:1 or 1.05:1, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0037] Preferably, the calcination in step (3) is carried out in an air atmosphere with a dew point of -20 to -40°C, for example, it can be -20°C, -25°C, -30°C, -35°C or -40°C, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0038] Since this invention uses a wet coating process, the high-nickel ternary material has already come into contact with the solvent during the coating process. In order to further ensure the structural stability of the ternary material, in conjunction with the aforementioned wet coating process, this invention uses dry air with low moisture content for calcination, thereby avoiding the damage of high-nickel ternary material to moisture in the air, and further improving the structural stability and electrochemical performance of the high-nickel ternary material.
[0039] Preferably, the calcination temperature in step (3) is 300-350℃, for example, it can be 300℃, 310℃, 320℃, 330℃, 340℃ or 350℃, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0040] The calcination temperature described in this invention affects the coating effect. If the calcination temperature is too low, the coating source cannot be effectively decomposed, that is, the non-metallic acid compounds and aluminum hydroxide cannot form a relatively stable complex. If the calcination temperature is too high, it will damage the coating material and an effective coating layer cannot be obtained.
[0041] Preferably, the holding time for calcination in step (3) is 6-10h, for example, 6h, 7h, 8h or 10h, and the heating rate is 3-5℃ / min, for example, 3℃ / min, 3.5℃ / min, 4℃ / min, 4.5℃ / min or 5℃ / min, but not limited to the listed values. Other unlisted values within the range are also applicable.
[0042] As a preferred embodiment of the preparation method of the present invention, the preparation method includes the following steps:
[0043] (1) Mix the non-metallic acid compound, aluminum hydroxide and solvent for 8-12 min to obtain the coating solution;
[0044] The non-metallic acid compound is boric acid, and the aluminum hydroxide is A-4 type aluminum hydroxide sol;
[0045] The content of the non-metallic acid compound is 0.5-1.5 wt% of the mass of the high-nickel ternary material in step (2), the content of the aluminum hydroxide is 1-3 wt% of the mass of the high-nickel ternary material in step (2), and the mass ratio of the solvent to the high-nickel ternary material in step (2) is (1-1.5):1.
[0046] (2) Mix the high-nickel ternary material with the coating solution described in step (1) for 8-12 minutes to obtain a mixture;
[0047] The method for producing the high-nickel ternary material includes: mixing a high-nickel ternary material precursor, a lithium source, and a dopant additive; sintering the mixture at 700-800°C for 12-16 hours in a pure oxygen atmosphere at a heating rate of 1-3°C / min to obtain the high-nickel ternary material; the content of the dopant additive is 0.05-0.5 wt% of the mass of the high-nickel ternary material precursor.
[0048] (3) The mixture described in step (2) is dried at a temperature of 120-180℃, and then calcined at 300-350℃ for 6-10 hours in an air atmosphere with a dew point of -20 to -40℃ at a heating rate of 3-5℃ / min to obtain the modified high-nickel ternary material.
[0049] In a second aspect, the present invention provides a modified high-nickel ternary material, which is obtained by the preparation method described in the first aspect.
[0050] Preferably, the chemical formula of the high-nickel ternary material is LiNi. x Co y Mn z M 1-x-y-z O2, wherein 0.8 ≤ x < 1.0, for example, can be 0.8, 0.85, 0.9, 0.95 or 0.98, 0 < y < 0.2, for example, can be 0.1, 0.15 or 0.19, 0 < z < 0.2, for example, can be 0.1, 0.15 or 0.19, and M includes any one or at least two combinations of Zr, Ti, Nb, Ce, Sr, Mg or W, with typical but non-limiting combinations including combinations of Zr and Ti, combinations of Nb and Ce, or combinations of Sr and Mg.
[0051] Thirdly, the present invention provides a lithium-ion battery comprising the modified high-nickel ternary material as described in the second aspect.
[0052] Compared with the prior art, the present invention has the following beneficial effects:
[0053] This invention uses non-metallic acid compounds and aluminum hydroxide as coating sources to make the coating solution acidic and avoid the damage to the structure of high-nickel ternary materials caused by wet coating. That is, this invention uses wet coating, which on the one hand can neutralize the residual alkali on the surface of high-nickel ternary materials, replacing the water washing process; on the other hand, as a coating mixing process, it avoids the process of mixing and coating after water washing, simplifying the water washing process and the coating process into a single step. In addition, the wet coating method of this invention has a good coating effect and avoids the disadvantages of uneven coating and self-agglomeration of coating agents in dry coating, thereby obtaining modified high-nickel ternary materials with high structural stability and excellent cycle performance. Attached Figure Description
[0054] Figure 1 This is a scanning electron microscope image of the modified high-nickel ternary material described in Example 1 of the present invention at a magnification of 5000x.
[0055] Figure 2 This is a scanning electron microscope image of the modified high-nickel ternary material described in Example 1 of the present invention at a magnification of 10,000.
[0056] Figure 3 The image is a scanning electron microscope image of the modified high-nickel ternary material described in Comparative Example 1 of the present invention at a magnification of 5000x.
[0057] Figure 4 This is a scanning electron microscope image of the modified high-nickel ternary material described in Comparative Example 1 of the present invention at a magnification of 10,000.
[0058] Figure 5 The images show the cycling curves of the modified high-nickel ternary materials described in Examples 1, 2, 3, Comparative Example 1, and Comparative Example 4 of this invention. Detailed Implementation
[0059] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.
[0060] Example 1
[0061] This embodiment provides a method for preparing a modified high-nickel ternary material, the method comprising the following steps:
[0062] (1) Mix the non-metallic acid compound, aluminum hydroxide and solvent for 8-12 min to obtain the coating solution;
[0063] The non-metallic acid compound is boric acid, the alumina hydroxide is A-4 type alumina hydroxide sol, and the solvent is water;
[0064] The content of the non-metallic acid compound is 0.5 wt% of the mass of the high-nickel ternary material in step (2), the content of the aluminum hydroxide is 1.09 wt% of the mass of the high-nickel ternary material in step (2), and the mass ratio of the solvent to the high-nickel ternary material in step (2) is 1.25:1.
[0065] (2) Mix the high-nickel ternary material with the coating solution described in step (1) for 10 minutes to obtain a mixture;
[0066] The high-nickel ternary material has a mass of 1000g and is prepared by mixing a high-nickel ternary material precursor, a lithium source, and doping additives, and sintering at 780℃ for 14h in a pure oxygen atmosphere at a heating rate of 2℃ / min to obtain the high-nickel ternary material. The doping additives are SrO and WO3, with SrO content being 0.35wt% of the mass of the high-nickel ternary material precursor and WO3 content being 0.45wt% of the mass of the high-nickel ternary material precursor. The chemical formula of the high-nickel ternary material precursor is Ni. 0.8 Co 0.1 Mn 0.1 (OH)2, wherein the lithium source is LiOH, and the molar ratio of lithium in the lithium source to nickel, cobalt and manganese in the high-nickel ternary material precursor is 1.04:1;
[0067] (3) The mixture described in step (2) is dried at 150°C, and then calcined at 300°C for 8 hours in an air atmosphere with a dew point of -30°C at a heating rate of 5°C / min to obtain the modified high-nickel ternary material.
[0068] The scanning electron microscope image of the modified high-nickel ternary material described in this embodiment at 5000x magnification is shown below. Figure 1 As shown, the scanning electron microscope image at 10,000x magnification is as follows: Figure 2 As shown in the figure, the cyclic curve is as follows Figure 5 As shown.
[0069] Example 2
[0070] This embodiment provides a method for preparing a modified high-nickel ternary material, the method comprising the following steps:
[0071] (1) Mix the non-metallic acid compound, aluminum hydroxide and solvent for 8 min to obtain the coating solution;
[0072] The non-metallic acid compound is boric acid, the alumina hydroxide is A-4 type alumina hydroxide sol, and the solvent is water;
[0073] The content of the non-metallic acid compound is 0.75 wt% of the mass of the high-nickel ternary material in step (2), the content of the aluminum hydroxide is 1.63 wt% of the mass of the high-nickel ternary material in step (2), and the mass ratio of the solvent to the high-nickel ternary material in step (2) is 1:1.
[0074] (2) Mix the high-nickel ternary material with the coating solution described in step (1) for 12 minutes to obtain a mixture;
[0075] The method for producing the high-nickel ternary material includes: mixing a high-nickel ternary material precursor, a lithium source, and doping additives; sintering the mixture at 700°C for 16 hours in a pure oxygen atmosphere at a heating rate of 1°C / min to obtain the high-nickel ternary material; the doping additives are ZrO2 and MgO, wherein the content of ZrO2 is 0.35 wt% of the mass of the high-nickel ternary material precursor, and the content of ZrO2 is 0.05 wt% of the mass of the high-nickel ternary material precursor; the chemical formula of the high-nickel ternary material precursor is Ni. 0.8 Co 0.1 Mn 0.1 (OH)2; the lithium source is LiOH, and the molar ratio of lithium in the lithium source to nickel, cobalt and manganese in the high-nickel ternary material precursor is 1.03:1;
[0076] (3) The mixture described in step (2) is dried at 120°C, and then calcined at 325°C for 10 hours at a heating rate of 5°C / min in an air atmosphere with a dew point of -20°C to obtain the modified high-nickel ternary material.
[0077] The cycling curve of the modified high-nickel ternary material obtained in this embodiment is as follows: Figure 5 As shown.
[0078] Example 3
[0079] This embodiment provides a method for preparing a modified high-nickel ternary material, the method comprising the following steps:
[0080] (1) Mix the non-metallic acid compound, aluminum hydroxide and solvent for 8 min to obtain the coating solution;
[0081] The non-metallic acid compound is boric acid, the alumina hydroxide is A-4 type alumina hydroxide sol, and the solvent is water;
[0082] The content of the non-metallic acid compound is 1.5 wt% of the mass of the high-nickel ternary material in step (2), the content of the aluminum hydroxide is 3 wt% of the mass of the high-nickel ternary material in step (2), and the mass ratio of the solvent to the high-nickel ternary material in step (2) is 1.5:1.
[0083] (2) Mix the high-nickel ternary material with the coating solution described in step (1) for 12 minutes to obtain a mixture;
[0084] The method for producing the high-nickel ternary material includes: mixing a high-nickel ternary material precursor, a lithium source, and doping additives; sintering the mixture at 800°C for 12 hours in a pure oxygen atmosphere at a heating rate of 2°C / min to obtain the high-nickel ternary material; the doping additives are ZrO2 and SrO, wherein the content of ZrO2 is 0.4 wt% of the mass of the high-nickel ternary material precursor, and the content of SrO is 0.3 wt% of the mass of the high-nickel ternary material precursor; the chemical formula of the high-nickel ternary material precursor is Ni. 0.8 Co 0.1 Mn 0.1 (OH)2; the lithium source is LiOH, and the molar ratio of lithium in the lithium source to nickel, cobalt and manganese in the high-nickel ternary material precursor is 1.04:1;
[0085] (3) The mixture described in step (2) is dried at 180°C, and then calcined at 350°C for 10 hours in an air atmosphere with a dew point of -40°C at a heating rate of 3°C / min to obtain the modified high-nickel ternary material.
[0086] The cycling curve of the modified high-nickel ternary material obtained in this embodiment is as follows: Figure 5 As shown.
[0087] Example 4
[0088] This embodiment provides a method for preparing a modified high-nickel ternary material. The preparation method is the same as in Example 1, except that the content of the non-metallic acid compound in step (1) is 0.3 wt% of the mass of the high-nickel ternary material in step (2).
[0089] Example 5
[0090] This embodiment provides a method for preparing a modified high-nickel ternary material. The preparation method is the same as in Example 1, except that the content of the non-metallic acid compound in step (1) is 1.8 wt% of the mass of the high-nickel ternary material in step (2).
[0091] Example 6
[0092] This embodiment provides a method for preparing a modified high-nickel ternary material. The preparation method is the same as in Example 1, except that the content of aluminum hydroxide in step (1) is 0.7 wt% of the mass of the high-nickel ternary material in step (2).
[0093] Example 7
[0094] This embodiment provides a method for preparing a modified high-nickel ternary material. The preparation method is the same as in Example 1, except that the content of aluminum hydroxide in step (1) is 3.5 wt% of the mass of the high-nickel ternary material in step (2).
[0095] Example 8
[0096] This embodiment provides a method for preparing a modified high-nickel ternary material. Except for the mass ratio of the solvent in step (1) to the high-nickel ternary material in step (2) being 0.8:1, the preparation method is the same as in Example 1.
[0097] Example 9
[0098] This embodiment provides a method for preparing a modified high-nickel ternary material. Except for the mass ratio of the solvent in step (1) to the high-nickel ternary material in step (2) being 1.8:1, the preparation method is the same as in Example 1.
[0099] Example 10
[0100] This embodiment provides a method for preparing a modified high-nickel ternary material. Except for step (1), where the alumina hydroxyl oxide is A-10 type alumina hydroxyl oxide sol, the preparation method is the same as in Example 1.
[0101] Example 11
[0102] This embodiment provides a method for preparing a modified high-nickel ternary material. Except for the calcination temperature of 250°C in step (3), the preparation method is the same as in Example 1.
[0103] Example 12
[0104] This embodiment provides a method for preparing a modified high-nickel ternary material. Except for the calcination temperature of 400°C in step (3), the preparation method is the same as in Example 1.
[0105] Example 13
[0106] This embodiment provides a method for preparing a modified high-nickel ternary material. Except for the dew point of the air atmosphere used for calcination in step (3) being -10°C, the preparation method is the same as in Example 1.
[0107] Comparative Example 1
[0108] This comparative example provides a method for preparing a modified high-nickel ternary material, the method comprising the following steps:
[0109] (1) Mix high-nickel ternary material and water at a mass ratio of 1:1 for 10 min, then filter and dry at 150°C to obtain dried material;
[0110] The preparation method of the high-nickel ternary material is the same as step (2) of Example 1;
[0111] (2) The dried material, alumina and boric acid described in step (1) are dry-mixed and then calcined at 300°C for 8 hours at a heating rate of 5°C / min to obtain the modified high-nickel ternary material; the boric acid is 0.5% of the mass of the dried material described in step (1) and the alumina is 0.3% of the mass of the dried material described in step (1);
[0112] The scanning electron microscope image of the modified high-nickel ternary material described in this comparative example at 5000x magnification is shown below. Figure 3 As shown, the scanning electron microscope image at 10000x magnification is as follows: Figure 4 As shown, the cyclic curve is as follows Figure 5 As shown.
[0113] Comparative Example 2
[0114] This comparative example provides a method for preparing a modified high-nickel ternary material. The preparation method is the same as in Example 1 except that no non-metallic acid compound is added in step (1).
[0115] Comparative Example 3
[0116] This comparative example provides a method for preparing a modified high-nickel ternary material. The preparation method is the same as in Example 1, except that in step (1), the hydroxyl aluminum oxide is replaced by aluminum oxide.
[0117] Comparative Example 4
[0118] This comparative example provides a method for preparing a high-nickel ternary material, which is the same as the method for preparing the high-nickel ternary material in step (2) of Example 1, without any coating modification;
[0119] The cycling curve of the high-nickel ternary material described in this comparative example is shown in the figure below. Figure 5 As shown.
[0120] The modified high-nickel ternary materials obtained in Examples 1-14 and Comparative Examples 1-3, as well as the high-nickel ternary material described in Comparative Example 4, were tested for their surface pH and the contents of Li2CO3 and LiOH. They were then prepared into positive electrode sheets, which were then assembled into lithium-ion batteries with lithium negative electrode sheets, lithium hexafluorophosphate electrolyte, and PE separators. The specific capacity was tested under the conditions of 2.5-4.25V and 0.2C, and the cycle retention rate was tested under the conditions of 3.0-4.5V and 0.5C / 0.1C for 50 cycles. The test results are shown in Table 1.
[0121] Table 1
[0122]
[0123]
[0124] The following points can be observed from Table 1:
[0125] (1) The modified high-nickel ternary material provided by the present invention has a low residual alkali content on the surface. The wet coating not only achieves uniform coating and significantly improves the cycling performance of the material, but also reduces the residual alkali on the surface of the material. As can be seen from Examples 1 and 4-7, the content of boric acid and aluminum hydroxide is within a reasonable range, which can further ensure the electrochemical performance of the material and make the removal of residual alkali and effective coating work together. As can be seen from Examples 1 and 8-9, the content of solvent during wet coating will affect the coating effect and the structural stability of the high-nickel ternary material. The mass ratio of solvent to high-nickel ternary material needs to be within a reasonable range to achieve the purpose of removing residual alkali, effective coating and ensuring the structural stability of the material. As can be seen from Examples 1 and 10, the present invention uses A-4 type aluminum hydroxide sol with acidity, which can further reduce residual alkali and improve the electrochemical performance of the material.
[0126] (2) As can be seen from Examples 1 and 11-12, the calcination temperature affects the effective decomposition and coating of the coating source, as well as the structural stability of the coating layer; as can be seen from Examples 1 and 13, if the moisture content of the calcination atmosphere is too high during the calcination process, it will affect the structural stability of the material, thereby affecting the electrochemical performance of the material; as can be seen from Examples 1 and Comparative Example 1, Comparative Example 1 uses water washing to remove residual alkali and uses a dry coating method, which is a complicated preparation process, and from... Figures 1-4 As can be seen from the comparison, the material obtained in Embodiment 1 of the present invention is as follows: Figure 1 and Figure 2 The surface coating shown is uniform, with no self-agglomeration or segregation of the coating material. In contrast, the coating material obtained by dry coating in Comparative Example 1 exhibits agglomeration, resulting in a decrease in the electrochemical performance of the material.
[0127] (3) As can be seen from Example 1 and Comparative Example 2, if the non-metallic acid compound boric acid is not added, the effect of removing residual alkali decreases, and the electrochemical performance of the obtained material also decreases because boron-aluminum compounds cannot be formed. As can be seen from Example 1 and Comparative Example 3, the present invention uses aluminum hydroxide as the coating source. Compared with alumina, aluminum hydroxide can be evenly dispersed in the solvent of wet coating, thereby achieving uniform coating, and can generate boron-aluminum compounds. Alumina is prone to agglomeration when the solvent is evaporated during wet coating. Therefore, the electrochemical performance of the material obtained in Comparative Example 3 decreases. As can be seen from Example 1 and Comparative Example 4, the modified coating of the present invention can effectively reduce residual alkali and improve electrochemical performance.
[0128] In summary, this invention provides a modified high-nickel ternary material, its preparation method, and its application. The preparation method employs a wet coating process, in which the high-nickel ternary material is dispersed and coated in a coating solution, followed by sintering. This eliminates the need for dry mixing and coating after water washing, simplifying the process of removing residual alkali and coating into a single step, thus shortening the material preparation process. Furthermore, it achieves good residual alkali removal and coating effects, significantly improving the electrochemical performance of the modified high-nickel ternary material.
[0129] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. A method for preparing a modified high-nickel ternary material, characterized in that, The preparation method includes the following steps: (1) Mix non-metallic acid compounds, aluminum hydroxide and solvent to obtain a coating solution; (2) Mix the high-nickel ternary material with the coating liquid described in step (1) to obtain a mixture; (3) The mixture described in step (2) is calcined to obtain the modified high-nickel ternary material; The non-metallic acid compound mentioned in step (1) includes boric acid; The hydroxyalumina mentioned in step (1) is A-4 type hydroxyalumina sol.
2. The preparation method according to claim 1, characterized in that, The content of the non-metallic acid compound in step (1) is 0.5-1.5 wt% of the mass of the high-nickel ternary material in step (2).
3. The preparation method according to claim 1, characterized in that, The content of aluminum hydroxide in step (1) is 1-3 wt% of the mass of the high-nickel ternary material in step (2).
4. The preparation method according to claim 1, characterized in that, The mass ratio of the solvent in step (1) to the high-nickel ternary material in step (2) is (1-1.5):
1.
5. The preparation method according to claim 1, characterized in that, The solvent in step (1) includes water.
6. The preparation method according to claim 1, characterized in that, The mixing time in step (1) is 8-12 minutes.
7. The preparation method according to claim 1, characterized in that, After the mixture described in step (2) is evaporated to dryness, it is then calcined as described in step (3).
8. The preparation method according to claim 7, characterized in that, The temperature for evaporation is 120-180℃.
9. The preparation method according to claim 1, characterized in that, The mixing time in step (2) is 8-12 minutes.
10. The preparation method according to claim 1, characterized in that, The method for preparing the high-nickel ternary material in step (2) includes: mixing the high-nickel ternary material precursor, lithium source and doping additives, and sintering to obtain the high-nickel ternary material.
11. The preparation method according to claim 10, characterized in that, The doping additives include any one or a combination of at least two of ZrO2, TiO2, Nb2O5, CeO2, SrO, MgO or WO3.
12. The preparation method according to claim 10, characterized in that, The content of the doping additive is 0.05-0.5 wt% of the mass of the high-nickel ternary material precursor.
13. The preparation method according to claim 10, characterized in that, The sintering temperature is 700-800℃.
14. The preparation method according to claim 10, characterized in that, The sintering time is 12-16 hours, and the heating rate is 1-3℃ / min.
15. The preparation method according to claim 10, characterized in that, The sintering is carried out in a pure oxygen atmosphere.
16. The preparation method according to claim 1, characterized in that, The calcination in step (3) is carried out in an air atmosphere with a dew point of -20 to -40°C.
17. The preparation method according to claim 1, characterized in that, The calcination temperature in step (3) is 300-350℃.
18. The preparation method according to claim 1, characterized in that, The holding time for calcination in step (3) is 6-10 hours, and the heating rate is 3-5℃ / min.
19. The preparation method according to any one of claims 1-18, characterized in that, The preparation method includes the following steps: (1) Mix non-metallic acid compounds, aluminum hydroxide and solvent for 8-12 min to obtain coating solution; The non-metallic acid compound is boric acid, and the aluminum hydroxide is A-4 type aluminum hydroxide sol; The content of the non-metallic acid compound is 0.5-1.5 wt% of the mass of the high-nickel ternary material in step (2), the content of the alumina hydroxide is 1-3 wt% of the mass of the high-nickel ternary material in step (2), and the mass ratio of the solvent to the high-nickel ternary material in step (2) is (1-1.5):
1. (2) Mix the high-nickel ternary material with the coating solution described in step (1) for 8-12 minutes to obtain a mixture; The method for producing the high-nickel ternary material includes: mixing a high-nickel ternary material precursor, a lithium source, and a dopant additive; sintering the mixture at 700-800°C for 12-16 hours in a pure oxygen atmosphere at a heating rate of 1-3°C / min to obtain the high-nickel ternary material; the content of the dopant additive is 0.05-0.5 wt% of the mass of the high-nickel ternary material precursor. (3) The mixture described in step (2) is dried at a temperature of 120-180℃, and then calcined at 300-350℃ for 6-10 hours in an air atmosphere with a dew point of -20~-40℃ at a heating rate of 3-5℃ / min to obtain the modified high-nickel ternary material.
Citation Information
Patent Citations
Method for coating high-nickel ternary material with aluminum oxide and boron oxide
CN108091830A
Modified ternary positive electrode material, and preparation method and application thereof
CN114005986A